Tinjauan Dampak Persaingan Toko Ritel antara Indomaret dan Alfamart terhadap Preferensi Konsumen di Kabupaten Kuningan - Efwan Zainul Ridwan; Dian Puspitasari; Elisah Rahmawati; Fika Khoirunnisa Kurnia Illahi; Gisa Alsakinah (Letterlijk, 2024)
Retail stores are a business that is classified as having the potential to reaps large profits. The increasing presence of these retail stores offers alternative choices for consumers' shopping activities. The purpose of this research is to find out consumer preferences in choosing the retail store they use as a place to shop in Kuningan Regency, as well as to find out what variables influence consumer preferences in choosing this retail store in Kuningan Regency. The population in this research is consumers of Indomaret and Alfamart retail stores in Kuningan Regency. The sample size used in this research was 33 consumers of Indomaret and Alfamart retail stores in Kuningan Regency. This type of research uses comparative research which aims to see differences in results from selected variables using a questionnaire on the sample. The research results show that there are significant differences between consumer preferences in choosing the retail store they need. Indomaret in Kuningan Regency must improve its quality to increase people's purchase intention. Keywords: Alfamart; Consumer Preferences; Indomaret